Boy soldiers of the American Revolution - Cox, Caroline, 1954-2014 (The University of North Carolina Press, 2016)
"Between 1819 and 1845, as veterans of the Revolutionary War were filing applications to receive pensions for their service, the government was surprised to learn that many of the soldiers were not men, but boys, many of whom were under the age of sixteen, and some even as young as nine. In Boy Soldiers of the American Revolution, Caroline Cox reconstructs the lives and stories of this young subset of early American soldiers, focusing on how these boys came to join the army and what they actually did in service. Giving us a rich and unique glimpse into colonial childhood, Cox traces the evolution of youth in American culture in the late eighteenth century, as the accepted age for children to participate meaningfully in society--not only in the military--was rising dramatically"--